2012
DOI: 10.3122/jabfm.2012.06.120066
|View full text |Cite
|
Sign up to set email alerts
|

"Building through the Grief": Vicarious Trauma in a Group of Inner-City Family Physicians

Abstract: Background: Vicarious trauma is an understudied phenomenon among Canadian family physicians.Objective: This phenomenological study set out to explore the experiences of a group of inner-city family physicians caring for women using illicit drugs.Methods: Ten family physicians working in Toronto and Ottawa, Canada, participated in in-depth interviews. The data were analyzed using an iterative and interpretive process.Results: The first major theme emerging from the data analysis was the emotional impact of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…In one study of inner-city family physicians caring for women using illicit drugs, Woolhouse et al [11] found emotional stress, isolation and characteristics of VT among participants. Even less is known about VT experienced by those who volunteer their time to conduct asylum evaluations or to work with torture survivors.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In one study of inner-city family physicians caring for women using illicit drugs, Woolhouse et al [11] found emotional stress, isolation and characteristics of VT among participants. Even less is known about VT experienced by those who volunteer their time to conduct asylum evaluations or to work with torture survivors.…”
Section: Introductionmentioning
confidence: 97%
“…Very little research has addressed VT in physicians [10,11] in general. In one study of inner-city family physicians caring for women using illicit drugs, Woolhouse et al [11] found emotional stress, isolation and characteristics of VT among participants.…”
Section: Introductionmentioning
confidence: 98%
“…Physicians and other healthcare providers come face to face with suffering on a daily basis that might be singularly life-changing and traumatic events for another sort of witness. The toll expresses itself in a number of ways and under a variety of different names, such as vicarious or secondary trauma, [1][2][3] occupational stress, 4 burnout, 5 or compassion fatigue. 1,6 Although all healthcare providers may experience these phenomena as occupational hazards, those who serve in identifiably more difficult contexts have the difficulty compounded by geographic (rural) or organizational isolation, relatively low compensation, poor or unsafe working conditions, or more draining patient interactions.…”
mentioning
confidence: 99%
“…1,6 Although all healthcare providers may experience these phenomena as occupational hazards, those who serve in identifiably more difficult contexts have the difficulty compounded by geographic (rural) or organizational isolation, relatively low compensation, poor or unsafe working conditions, or more draining patient interactions. 2,7 Fortunately, physicians tend to be resilient individuals. As Reed 8 and colleagues demonstrate, primary care and specialist physicians, in both rural and nonrural settings, demonstrate similar levels of grit, 8 -10 defined as "perseverance and passion for long-term goals, working strenuously toward challenges, and maintaining effort and interest over years despite failure, adversity, and plateaus in progress."…”
mentioning
confidence: 99%
“…Do physicians experience vicarious traumatic stress after observing various aspects of trauma experienced by their patients? Woolhouse 16 used qualitative methods to explore the feelings of Canadian family physicians caring for inner-city women with substance use. The authors do very well at pulling out some of the compelling comments and thoughts of the family physicians in these practice settings and the mechanisms they use to deal with the vicarious trauma they experience.…”
Section: New Thoughts and Datamentioning
confidence: 99%